Comparison of insertion time, pull-out strength, and screw-media interface area of customized pedicle screw with different core and thread design against commercial pedicle screw: a pilot study on Indonesian Population - Magetsari, Rahadyan (BioMed Central Ltd, 2022)
Objective: This research aimed to developing customized pedicle screw based on Indonesian vertebral anatomy and compare the insertion time, pull-out strength, and screw-media interface area of different screw design. We have developed 3 different types of pedicle screws (v-thread cylinder-core, square-thread cylinder-core and square-thread conical-core). The thread diameter was calculated from pedicle width of Indonesian population (6 mm). We used commercially available pedicle screw as control group (6.2 mm). Result: The insertion time were significantly difference between v-thread cylinder-core pedicle screw (22.94 s) with commercially available pedicle screw (15.86 s) (p < 0.05). The pull-out strength was significantly difference between commercially available pedicle screw (408.60 N) with square-thread conical pedicle screw (836.60 N) (p < 0.05). The square-thread conical-core group have the highest interface area (1486.21 mm2). The data comparison showed that the square-thread conical-core customized pedicle screw group has comparable insertion time and has better pull-out strength than commercially available pedicle screw.